The Effect Corporate Governance Toward Islamic Social Reporting (ISR): Profitability as a Mediating - Ganis Bina Desy Ariyani (Profesional Muda Cendekia Publishing, 2020)
The Purpose of this research is to determine the role of profitability as a intervening between corporate governance on the disclosure of ISR in Islamic Commercial Banks (BUS) in Indonesia in the 2014-2018 period. This research uses quantitative research using multiple linear regression analysis. This study uses secondary data in the form of panel data on companies registered in BUS for the 2014-2018 period. The population in this study is BUS in Indonesia during the 2014-2018 period. The sampling method is carried out by purposive sampling using several criteria to obtain 12 BUS used as research samples. The results of this study indicate that independent commissioners have an effect on ISR, while managerial ownership, audit committees, profitability have no effect on ISR. Managerial expertise, independent commissioners, and audit committees do not affect profitability. Path Analysis results show that profitability cannot mediate the effect of managerial ownership, independent commissioners, and audit committees on the disclosure of Islamic ocial reporting (ISR).